24-hour metabolic profiles in diabetic children. Issue 2 (February 1980) - Griffin, N K; Spanos, A; Jenkins, P A; Turner, R C; Werther, G; Baum, J D
Abstract : 15 metabolic profiles were performed on 10 diabetic children who were on once-daily injections of insulin. Blood and urine glucose concentrations were high throughout much of the day and night, and were associated with abnormal levels of blood ketones, lactate, and pyruvate. The plasma free-insulin profiles gave a characteristic pattern for each type of insulin. The investigation gives valuable information for the clinical management of such children.